From personal survival to public health: community leadership by men who have sex with men in the response to HIV. - Trapence, Gift; Collins, Chris; Avrett, Sam; Carr, Robert; Sanchez, Hugo; Ayala, George; Diouf, Daouda; Beyrer, Chris; Baral, Stefan D (Lancet, 2012)
Community leadership and participation by gay men and men who have sex with men (MSM) have been central to the response to HIV since the beginning of the epidemic. Through a wide array of actions, engagement of MSM has been important in the protection of communities. The connection between personal and community health as drivers of health advocacy continue to be a powerful element. The passion and urgency brought by MSM communities have led to the targeting and expansion of HIV and AIDS research and programming, and have improved the synergy of health and human rights, sustainability, accountability, and health outcomes for all people affected by HIV. MSM are, however, frequently excluded from the evidence-based services that they helped to develop, despite them generally being the most effective actors in challenging environments. Without MSM community involvement, government-run health programmes might have little chance of effectively reaching communities or scaling up interventions to lessen, and ultimately end, the HIV pandemic.
Keywords: Delivery of Health Care; Health Knowledge, Attitudes, Practice; HIV Infections; Homosexuality, Male; Humans; International Cooperation; Leadership; Male; Public Health; Sexual Behavior